The interrelation between headaches and the online behavior of adolescents and young people of the Republic of Tuva - Evert, Lydia S.; Kostyuchenko, Yulia R.; Seren-ool, Sayana S. (The New Research of Tuva, 2024)
The article analyzes one of the clinical forms of primary headache (tension-type headache, TTH) in adolescents and young people in Tuva, as well as its comorbid associations with different types of online behavior and assesses their role as potential predictors of headache development. The importance of this work stems from the high prevalence of TTH among adolescents and young adults in many countries, as well as the frequent association between this condition and maladaptive online behavior. Additionally, there is a high risk of developing chronic headache if appropriate diagnosis and prevention strategies are not implemented for this group of individuals. The aim of the study was to investigate the associations between TTH and various types of internet use (adaptive, maladaptive, and pathological) as well as the characteristics of the internet content consumed among Tuvan adolescents and young people of different ages, genders, and ethnicities. The analysis is based on the results of online surveys conducted among adolescents and young adults in Tuva between January and September 2023, with a total sample size of 2,488 participants. A comparative analysis of the indicators in the overall sample and in subgroups divided by gender and ethnicity (Tuvan and Russian) is presented. The prevalence of headache was found among all surveyed participants (14.2%), with a higher prevalence among Russians (22.6% and 12.9%) and girls (15.7% and 12.2%). The age group of 15–18 years also showed a higher prevalence (15.6%, 13.6%, and 4.5%). Close associations between headache and maladaptive online behaviors, such as problematic internet use and non-problematic internet use, as well as a mixed and undifferentiated form of problematic internet use, were revealed. Additionally, dependence on smartphones, computer games, and social networks was also found to be associated with headache. The significant role of these factors as predictors of headache in different age, gender, and ethnic groups was established.